Performance maps for an air-standard irreversible Dual-Miller cycle (DMC) with late inlet valve closing (LIVC) version - Gonca, Guven; Sahin, Bahri; Ust, Yasin (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In this paper, a performance analysis based on the power output, thermal efficiency, maximum power output (MP) and maximum thermal efficiency (MEF) criteria have been carried out for an air-standard irreversible Dual-Miller cycle (DMC) with late inlet valve closing (LIVC) version which covers internal irreversibility owing to the irreversible-adiabatic processes. The thermal efficiency and power output are acquired based on the stroke ratio, cut-off ratio, pressure ratio, miller cycle ratio, cycle temperature ratio, cycle pressure ratio and the isentropic efficiencies of compression and expansion processes of the cycle. The influences of cycle temperature ratio and cycle pressure ratio of the DMC on the optimum performances are examined. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Miller cycle; Performance analysis; Optimization; Power output; Thermal efficiency; Irreversible; DIESEL-ENGINE; THERMODYNAMIC SYSTEMS; OPTIMAL PATHS; NOX EMISSION; EFFICIENCY; SIMULATION; Thermodynamics; Energy & Fuels